2018
DOI: 10.19030/jabr.v34i3.10166
|View full text |Cite
|
Sign up to set email alerts
|

The Influence Of Firm’s Fair Value System On Earnings Quality Under IFRS

Abstract: This paper analyzes the influence of firms’ fair value system on earnings quality under IFRS. Korean firms are required to adopt IFRS in 2011. IFRS adoption was expected to increase value relevance of book value of equity and benefit information users’ decision making. However, prior Korean studies report that value relevance of book value of equity is indifferent between under K-GAAP and IFRS. We consider that the indifference in value relevance of book value of equity after IFRS adoption is due to different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…This result is in line with the result of the research of Annisa & Taqwa (2020). However, this result is not in line with the result of Pompili & Tutino (2019), Rhee et al (2018), Tutino & Pompili (2018), Šodan (2015), Palasari (2018), Takacs et al (2020), andMauro et al (2017). This difference is presumed to occur because this study uses a total fair value proxy as used in the research of Annisa & Taqwa (2020), while other research uses various proxies to measure fair value.…”
Section: Resultsmentioning
confidence: 49%
See 3 more Smart Citations
“…This result is in line with the result of the research of Annisa & Taqwa (2020). However, this result is not in line with the result of Pompili & Tutino (2019), Rhee et al (2018), Tutino & Pompili (2018), Šodan (2015), Palasari (2018), Takacs et al (2020), andMauro et al (2017). This difference is presumed to occur because this study uses a total fair value proxy as used in the research of Annisa & Taqwa (2020), while other research uses various proxies to measure fair value.…”
Section: Resultsmentioning
confidence: 49%
“…Fair value measurement gives managers more discretion over the valuation of assets and liabilities; also, fair value is more difficult and expensive to audit (Benston, 2008). Pompili & Tutino (2019), Rhee et al (2018), Tutino & Pompili (2018), Šodan (2015), dan Palasari (2018) found that earnings can reduce earnings quality. H1: Fair value has a negative effect on earnings quality.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations